ENHANCED BIOPRODUCTION OF HYDROGEN BY ALGINATE IMMOBILIZED CELLS OF A PURPLE NON-SULPHUR BACTERUM RHODOCYCLUS TENUIS KU 017. - SRINIVAS MUNJAM; K. JYOTHI RANI (International Journal of Pharma and Bio Sciences, 2014)
Preliminary investigations on photoproduction of hydrogen by free viable cells of Rhodocyclus tenuis KU 017, and immobilized cells in sodium alginate matrix, under different cultural conditions with various carbon and nitrogen sources were carried out. Growing cells produced more amount of hydrogen under aerobic dark than aerobic light conditions. In contrast, under anaerobic conditions, hydrogen production was more in light than dark. Actively growing cells were more efficient and sustained hydrogen production for longer period than resting cells. Resting cells preferred light anaerobic conditions for hydrogen production. Resting cells required more lag period for hydrogen production, while growing cells produced more hydrogen during early phase of growth. Immobilization of bacterial cells not only enhanced hydrogen production but enabled the cells to produce hydrogen over an extended period. Among carbon sources formate induced maximum production of hydrogen at 96h and among nitrogen sources ammonium chloride induced maximum production at 192h incubation period. Lactate and L-tyrosine were poor carbon and nitrogen sources respectively for hydrogen production.